Integrative genomic analyses of APOBEC-mutational signature, expression and germline deletion of APOBEC3 genes, and immunogenicity in multiple cancer types - Zhishan Chen; Wanqing Wen; Jiandong Bao; Krystle L. Kuhs; Qiuyin Cai; Jirong Long; Xiao-ou Shu; Wei Zheng; Xingyi Guo (BMC, 2019)
Abstract Background Although APOBEC-mutational signature is found in tumor tissues of multiple cancers, how a common germline APOBEC3A/B deletion affects the mutational signature remains unclear. Methods Using data from 10 cancer types generated as part of TCGA, we performed integrative genomic and association analyses to assess inter-relationship of expressions for isoforms APOBEC3A and APOBEC3B, APOBEC-mutational signature, germline APOBEC3A/B deletions, neoantigen loads, and tumor infiltration lymphocytes (TILs). Results We found that expression level of the isoform uc011aoc transcribed from the APOBEC3A/B chimera was associated with a greater burden of APOBEC-mutational signature only in breast cancer, while germline APOBEC3A/B deletion led to an increased expression level of uc011aoc in multiple cancer types. Furthermore, we found that the deletion was associated with elevated APOBEC-mutational signature, neoantigen loads and relative composition of T cells (CD8+) in TILs only in breast cancer. Additionally, we also found that APOBEC-mutational signature significantly contributed to neoantigen loads and certain immune cell abundances in TILs across cancer types. Conclusions These findings reveal new insights into understanding the genetic, biological and immunological mechanisms through which APOBEC genes may be involved in carcinogenesis, and provide potential genetic biomarker for the development of disease prevention and cancer immunotherapy.